Social research & reflexivity content, consequences and context - May, Tim, 1957-; Perry, Beth. (Los Angeles, [Calif.] ; London : SAGE, 2011)
What are the critical gaps in thinking about reflexivity and social research? How is reflexive practice shaped by the contexts and cultures in which researchers work? How might research practice respond to twin demands of excellence and relevance in the knowledge-based economy?
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research; Self-knowledge, Theory of